Risk perception of medicinal marijuana in medical students from northeast Mexico [version 1; referees: awaiting peer review] - Castillo Guzmán, Sandra; Palacios Ríos, Dionicio; Nava Obregón, Teresa Adriana; Arredondo Mendoza, Julio C.; Alcalá Alvarado, Olga V.; Alonso Bracho, Sofía A.; Becerril Gaitán, Daniela Alejandra; González Santiago, Omar (Universidad Autónoma de Nuevo León, 2017)
Background. Several studies have shown support from the public toward the use of medicinal marijuana. In this cross-sectional study, we assess the risk perception to medicinal marijuana in a sample of medical students. Methods. To estimate risk perception, a visual scale that ranges from 0 cm (without risk) to 10 cm (totally risky) was used. Risk perception was expressed as the median of the cm marked over the scale. Differences among groups was tested with the Mann-Whitney and Kruskal-Wallis tests, as appropriate. Results. 283 students participated in the study. Risk perception to medicinal marijuana was 4.22, paracetamol 1.56 and sedatives 5.0. A significant difference in risk perception was observed in those that self-reported to smoke and consume alcohol. Conclusions. Risk perception of medicinal marijuana is 4.22 in medical students of northeast of Mexico. Students may underestimate its adverse effects. More studies with respect to this are needed.